Hepatitis C Transmission after Prostate Biopsy - Karim Ferhi; Morgan Rouprêt; Pierre Mozer; Guillaume Ploussard; Alain Haertig; Alexandre de La Taille (Case Reports in Urology)
Prostate biopsy is a current and well-codified procedure; antibiotic prophylaxis and rectal enema limit the risk of infection. To date, there has been no reported viral transmission between patients due to a contaminated ultrasound probe. In this study, we report the case of a patient who contracted the hepatitis C virus after transrectal prostate biopsy as part of an individual screening for prostate cancer.